2017
DOI: 10.1111/jai.13280
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional profile of soakedCajanus cajan(L.) Millsp. and its utilization as partial replacement for soybean meal in the diet ofClarias gariepinus(Burchell, 1822) fingerlings

Abstract: Summary This study aimed to investigate the efficacy of soaking as a cheap processing method in improving the nutritional utilization of Cajanus cajan for partial replacement of soybean meal in formulated diets of the African catfish Clarias gariepinus (Burchell, 1822). The nutrient profile of soaked C. cajan revealed a significant reduction (≤50%) in all anti‐nutritional factors. Proximate and amino acids were also affected by this processing method. Six practical diets (35 g/kg crude protein, 19.1 KJ/g diet)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Moreover, some plant-derived forages with high nutritional value and that are rich in amino acids have been widely developed and utilized. Recently, cotton meal [9], soybean meal and peanut meal [10,11] have been widely used in aquaculture feed and are very valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some plant-derived forages with high nutritional value and that are rich in amino acids have been widely developed and utilized. Recently, cotton meal [9], soybean meal and peanut meal [10,11] have been widely used in aquaculture feed and are very valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean by-products, mainly defatted soybean meal, have been widely used as surrogate protein source to fishmeal, although the main ANFs, such as enzyme inhibitors and saponins, have been frequently associated to low digestibility of diets. ANFs can be inactivated by processing techniques (grinding, cooking, extracting, fermenting) yielding quality products (Solomon et al, 2017), such as ethanol-extracted soybean protein concentrate (SPC), an alternative protein source for carnivorous fish diets ( Collins et al, 2013;Bañuelos-Vargas, 2014;Bansemer et al, 2015). Except for polysaccharides, most carbohydrates are washed off from SPC during processing; however, peptidic compounds are preserved, increasing crude protein contents of feedstuff and favoring its use in dense diets.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the observation reported by Johnson et al [ 30 ] for J. curcas seed soaked for up to seven days. The report of Kajihausa et al [ 24 ] and Solomon et al [ 25 ] also found that soaking was effective in improving the nutritional composition of sprouted sesame seed flour and pigeon pea Cajanus cajan , respectively. Fat and ash were, however, observed to be reduced in the soaked JCK and were thought to have been leached in the water which was subsequently drained off.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of NFRs in the latter category can be improved by various processing methods [ 21 ]. While some processing methods can increase the cost of feed production (due to the extra energy needed for thermal and mechanical processing), soaking is one of the few low-cost and simplistic methods that can be used for the processing of NFRs [ 22 , 23 , 24 , 25 ]. However, compared to other methods, this appears to be the least researched for the detoxification of many NFRs, perhaps because they are thought to be ineffective against thermolabile antinutrients.…”
Section: Introductionmentioning
confidence: 99%